Od polityki i teorii do literatury. Wokół „Théorie d'ensemble" grupy Tel Quel - Dziadek, Adam (Przestrzenie Teorii, 2007)
This text aims at a description of the famous manifesto published by the group Tel Quel in France in 1968. The author gives a short analysis of chosen texts by Michel Foucault, Jacques Derrida, Roland Barthes and particularly Julia Kristeva. The analysis shows important links between politics and literary theory of the Tel Quel. It also shows the way that politics and theory (based on such intertexts as Marx, Freud and Lacan) influenced new notion of the text, of the intertextuality and the others.